Medical Informatics: Searching for Underlying Components - Musen, M. A. (Methods of Information in Medicine, 2002)
Objective: To discuss unifying principles that can provide a theory for the diverse aspects of work in medical informatics. If medical informatics is to have academic credibility, it must articulate a clear theory that is distinct from that of computer science or of other related areas of study.Results: The notions of reusable domain ontologies and problem-solving methods provide the foundation for current work on second-generation knowledge-based systems. These abstractions are also attractive for defining the core contributions of basic research in informatics. We can understand many central activities within informatics in terms defining, refining, applying, and evaluating domain ontologies and problem-solving methods.Conclusion: Construing work in medical informatics in terms of actions involving ontologies and problem-solving methods may move us closer to a theoretical basis for our field.
Keywords: Medical informatics; computing methodologies; artificial intelligence; academic training; professional training